Cross slope gait biomechanics for individuals with and without a unilateral transtibial amputation. (August 2022) - Sinitski, Emily; Baddour, Natalie; Gholizadeh, Hossein; Besemann, Markus; Dudek, Nancy; Lemaire, Edward
Abstract: Background: This research was conducted to better understand compensatory strategies during cross-slope walking for adults with and without a unilateral transtibial amputation. Methods: Fourteen individuals with unilateral transtibial amputation and 14 individuals with no lower limb amputation participated in this study. Motion and force data were captured while participants walked on a treadmill in a virtual reality environment for level and ± 5° cross slopes. Temporal-spatial parameters, kinematics (ankle, knee, hip, pelvis, trunk), and ground reaction forces were examined. Findings: Compared to level, participants had similar step width but slightly longer steps for top-cross-slope and slightly shorter steps for bottom-cross-slope. Top-cross-slope required a more flexed limb with ankle eversion, and bottom-cross-slope required a more extended limb with ankle inversion. Participants had similar lateral pelvis and trunk motion for all walking conditions, but slightly more anterior trunk lean for top cross-slope with more anterior trunk lean observed for individuals with a lower limb amputation than without lower limb amputation. Participants with a lower limb amputation compensated for limited prosthetic ankle-foot dorsiflexion on the top-cross-slope by increasing prosthetic side hip flexion, reducing intact ankle/knee flexion, and increasing intact push-off force. Interpretation: Gait adaptations during cross-slope walking were primarily in the lower extremities and were largely similar for those with and without a transtibial amputation. The information presented in this paper provides a better understanding of gait strategies adopted during cross-slope walking and can guide researchers and industry in prosthetic development. Highlights: Gait adaptations during cross-slopes were primarily in the lower extremities. Gait adaptations were largely similar for those with and without a transtibial amputation. An asymmetric gait may help to minimize upper body motion during cross-slopes.